2023
DOI: 10.15407/exp-oncology.2023.01.028
|View full text |Cite
|
Sign up to set email alerts
|

ABERRANT EXPRESSION OF COL14A1, CELRS3, and CTHRC1 IN BREAST CANCER СELLS

Abstract: Background: Collagens, which are the major components of the extracellular matrix involved in the regulation of tumor microenvironment, could be differentially expressed in breast cancer (BC) with different transcriptome profiling. Aim: To analyze the transcript level expression of COL1A1, COL5A1, COL10A1, COL11A1, COL12A1, COL14A1, CTHRC1, and CELRS3 genes and the clinical relevance of their differential expression in BC. Materials and Methods: The transcript level expression of the genes was analyzed using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Overall, these findings provide further evidence for the role of CTHRC1 in glioma and its involvement in tumor cell migration. 14 - 16 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, these findings provide further evidence for the role of CTHRC1 in glioma and its involvement in tumor cell migration. 14 - 16 …”
Section: Discussionmentioning
confidence: 99%
“… 13 In recent years, abnormal expression of CTHRC1 has been observed in some tumors and is closely related to the survival prognosis of cancer patients. 14 - 16 Studies have shown that CTHRC1 is associated with the invasiveness of glioma cell lines, and knocking down CTHRC1 can reduce glioma cell invasion. 17 , 18 However, research on the role of CTHRC1 in gliomas is limited, and its exact function, particularly its clinical significance, is not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…An aberrant expression of ADAMTS and collagen gene families has been observed in some pathological conditions, including cancer, and has been related to both oncogenic and tumor-protective roles (Rocks et al 2006 ; Cal and López-Otín 2015 ; Xu et al 2019 ). Recent reports suggest that ADAMTS2 is overexpressed by gastric cancer cells, COL14A1 is downregulated in breast cancer cells, and ADAMTS15 functions as a tumor suppressor role in prostate cancer (Jiang et al 2019 ; Binder et al 2020 ; Malvia et al 2023 ). Even if the relationship between these proteins and the formation of equine sarcoids remains unclear, it is conceivable (as shown for matrix metalloproteinases—MMPs) that these proteins contribute to the remodeling and degradation of the extracellular matrix (ECM)—one of the factors linked to the processes of tumor initiation and progression.…”
Section: Discussionmentioning
confidence: 99%
“…To examine the above hypothesis, we first examined DEGs identified from the RNAseq analysis of FOXA1KD-SKBR3 cells and controls. Interestingly, among the top five upregulated genes in FOXA1KD (Supplementary table 3), four genes (ABCG2, COL14A1, FSCN1, and SLC2A3) have been associated with drug resistance, poor progression, metastasis and EMT in breast cancer, respectively (30)(31)(32)(33). Furthermore, overrepresentation analysis of the top 563 upregulated genes in FOXA1KD (log2 fold change > 5 and adjusted p-value < 0.01) using EnrichR revealed a significant enrichment for four Hallmark gene sets from Molecular Signatures Database (MSigDB).…”
Section: Foxa1 Is Required For Luminal Identity In Her2-positive Brea...mentioning
confidence: 99%